Monthly Dynamics of Cases of Laryngotracheitis and Recurrent Laryngotracheitis in Children and their Relation to Respiratory Viruses - Stanislavchuk L. (Львівський клінічний вісник)
Introduction. One of the most common syndromes in pediatrics is stenotic laryngotracheitis (SLT), in which genesis has a leading role in viruses, and is also characterized by certain seasonal rhythms. In contrast to SLT, recurrent stenotic laryngotracheitis (RSL) is considered by some authors as a polyphaktorial disease in which pathogenesis has chronic allergic inflammation with respiratory tract hyperuricaemia, immunological disorders, genetic predisposition and persistence of some pathogens (viruses of influenza, parainfluenza, adenoviruses, respiratory-syncytial viruses (rs-viruses), chlamydia). Aim. To study (on the results of long-term observation) the monthly dynamics of the occurrence of SLT and RSL compared to the analogical dynamics in case of the presence of respiratory viruses. Materials and methods. The analysis of cases of SLT (1-3 episodes of the disease) and RSL (4 episodes of the disease and more) was performed in a cohort of children 1995-1999 years of birth for the period 1995-2008 in Vinnitsa on the basis of materials of the Ambulance Station and the Regional Clinical Infectious Disease Hospital. The spectrum of respiratory viruses (virus viruses, paraghirs, adenoviruses, rs-viruses), was detected by the direct immunofluorescence analysis (ELISA) in smears from the nasal mucosa in children with SLT and RSL. Results. It was found out that the cases of SLT occurred during the year with the highest rate in March and October, and with the lowest rate in the summer months. Unlike the SLT fluctuations the RSL fluctuations were less pronounced, with a peak in October and with a fall in May, July and August. Parainfluenza viruses were dominated among the pathogens identified in patients with SLT and RSL. The curve of monthly dynamic of the cases of SLT coincided with the curve of the dynamic of positive results of immunofluorescent assay on parainfluenza viruses. These data indicated a dominant role of parainfluenza viruses in the genesis of SLT. Dynamics of the cases of RSL coincided with the dynamics of parainfluenza viruses only in October (peak), and with the dynamics of all detected viruses in March (increase) and in July (decrease). There were no clear patterns between the curves of respiratory viruses and the curve of RSL in the other months. These data indicated the significant role of other factors in the development of RSL. Conclusions. Parasitic viruses play a decisive role in the genesis of SLT. The peak of the monthly dynamics of cases of RSL (October) coincided with the rise of the curve of the dynamics of the parainfluenza virus.